Cauda equina, conus medullaris and syndromes mimicking sciatic pain: WFNS spine committee recommendations - Sandeep Vaishya; Mirza Pojskic; Manbachan Singh Bedi; Joachim Oertel; Christoph Sippl; Scott Robertson; Corinna Zygourakis (World Neurosurgery: X, 2024)
Introduction: Cauda equina syndrome (CES), conus medullaris syndrome (CMS), and sciatica-like syndromes or “sciatica mimics” (SM) may present as diagnostic and/or therapeutic dilemmas for the practicing spine surgeon. There is considerable controversy regarding the appropriate definition and diagnosis of these entities, as well as indications for and timing of surgery. Our goal is to formulate the most current, evidence-based recommendations for the definition, diagnosis, and management of CES, CMS, and SM syndromes. Methods: We performed a systematic literature search in PubMed from 2012 to 2022 using the keywords “cauda equina syndrome”, “conus medullaris syndrome”, “sciatica”, and “sciatica mimics”. Standardized screening criteria yielded a total of 43 manuscripts, whose data was summarized and presented at two international consensus meetings of the World Federation of Neurosurgical Societies (WFNS) Spine Committee. Utilizing the Delphi method, we generated seven final consensus statements. Results and conclusion: s: We provide standardized definitions of cauda equina, cauda equina syndrome, conus medullaris, and conus medullaris syndrome. We advocate for the use of the Lavy et al classification system to categorize different types of CES, and recommend urgent MRI in all patients with suspected CES (CESS), considering the low sensitivity of clinical examination in excluding CES. Surgical decompression for CES and CMS is recommended within 48 h, preferably within less than 24 h. There is no data regarding the role of steroids in acute CES or CMS. The treating physician should be cognizant of a variety of other pathologies that may mimic sciatica, including piriformis syndrome, and how to manage these.